Analytical Solution of Laminar Boundary Layer Equations Over A Flat Plate by Homotopy Perturbation Method - Majidian, Alireza; khaki, M.; khazayinejad, M. (International Journal of Applied Mathematical Research, 2012)
In this paper, the problem of an incompressible viscous flow over a flat plate is presented. The Homotopy perturbation method (HPM) is employed to solve the well-known Blasius nonlinear differential equation. It has been tried to use a special technique by which one be able to obtain solutions that are very close to the exact solution of the equation. The obtained results have been compared with the exact solution of Blasius equation and another results obtained in previous works so that the high accuracy of results are clear. Also it is found that this method is powerful mathematical tool and can be applied to a large class of linear and nonlinear problems in different fields of science and engineering especially some fluid mechanics equations.